Pendidikan Budi Pekerti Lintas Agama dalam Geguritan Krama Slam - Sugiharta, I Putu Suweka Oka (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Partial understanding of religious teachings often makes its adherents feel differences without common ground with adherents of other religions. This leads to an attitude of false acceptance and outright hatred towards adherents of other religions. When the holy scriptures are interpreted incorrectly, it is as if there is an absolute dichotomy between humans who have the same basic characteristics. For the purpose of eliminating this detrimental sense of difference, humans must reach maturity in religion. Every religious follower must keep away bad thoughts about other religions. The aim of studying aspects of cross-religious character in the Geguritan Krama Slam is to remind, since in the past, universal moral values have been emphasized in every religion. Its most obvious manifestation is seen in the sincere mutual respect between religious believers. Apart from being able to strengthen social cohesion, this can also convey the image that religion truly teaches noble values. This research is qualitative because it does not involve processing complicated numbers and measurements. The approach used is hermeneutics, with the aim of interpreting the contents of the text correctly. The results of this research are that in Geguritan Krama Slam, it is emphasized that universal moral teachings must be inherited continuously, there is a unified view across religions regarding moral character, moral teachings are the most valuable heritage, and religious teachings containing moral values must be maintained.